Content validity of men's u-21 soccer physical test - Yuliance Adii; Tri Setyo Guntoro; Sutoro Sutoro; Dewi Nurhidayah; Japhet Ndayisenga (Jurnal Keolahragaan, 2023)
The purpose of this study was to test the content validity of the men's U21 football physical test. This research is a quantitative descriptive research with survey techniques using the delphy method. The sample in this study consisted of 7 experts, namely 2 physical condition experts, 2 football game experts, 2 soccer coaches, and 1 analyzer of the input results of each expert. A self design rubric used as an instrument in this study. The data analysis technique in this study uses the aiken-v formula. The finding showed the men's U21 football physical test has high content   validity based on expert’s mutual agreement. The experts validation showed high validity (r=1.0) for BMI test to measure body composition and Sit and Reach test to measure flexibility. 30 meter sprint test for speed, leg and back dynamometer test to measure strength and shuttle run for agility showed high validity value r= 0.89. The aerocic test using MFT test also have high validity (r=0.83). This reseach indicate that the test battery for men's U21 football players is relevant and able to measure their physical ability to perform well in the game. This fitness test battery need to be reviewed continously based on the current demand and requirement.